The Conflict Management Strategies in Improving Madrasah Organizational Culture: A Case Study - Alip Almahdi; Abdurrahman Abdurrahman (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to analyze how the characteristics and organizational culture, types of conflict, and conflict management are used. The research method uses a qualitative method with a phenomenological approach. The research subjects included school principals and teachers at Madrasah Aliyah Ibrahimy Wali Songo Situbondo. Data collection techniques through interviews and observations, while data analysis techniques use triangulation. The results showed that the characteristics and organizational culture at Madrasah Aliyah Ibrahimy Wali Songo Situbondo were divided into communication, behavioural standards, and efforts to improve organizational climate. The types of conflicts are influenced by the corporate culture of the Madrasah Aliyah Ibrahimy Walisongo, which then causes conflicts within themselves, disputes between individuals, and conflicts between groups. The management of conflict handling is resolved through three strategies, namely collaboration, accommodation, and compromise. This research can provide recommendations on the management of conflict management that often occurs in the organizational culture of Madrasahs.